KARAKTERISTIK SERPIH MINYAK PADA FORMASI SINAMAR BERDASARKAN DATA PENGEBORAN BRP-02 DI DAERAH RANTAU PANDAN PROVINSI JAMBI: CHARACTERISTICS OF OIL SHALES IN SINAMAR FORMATION BASED ON BRP-02 DRILL HOLE DATA AT RANTAU PANDAN AREA JAMBI PROVINCE - Tobing, Robet Lumban (Buletin Sumber Daya Geologi, 2021)
Oil shales is defined as fine sedimentary rock that contains organic material and can produce oil when extracted. The Sinamar Formation in the study area is thought to be a carrier for oil shales. This formation is located in the western and southeastern parts of the study area and is thought to have age of Oligocene. Based on BRP-02 well data, lithology of the study area consists of shales, siltstone, sandstone and carbonaceous clays. The purpose of this study was to determine the character of the oil shales in the Sinamar Formation, which is scattered in the Rantau Pandan area, Bungo Regency, Jambi Province. As many as 25 samples of rock obtained from drilling wells were analyzed for maceral, pyrolysis, total organic carbon (TOC) and extraction of rock. The results of the maceral analysis show that the rock samples are dominated by liptinite maceral. TOC analysis show that the organic material in the samples is about 3.40 to 17.60% which is potentially good to very good as hydrocarbon source rock. The level of organic maturity is immature to over maturity. Based on the rock extraction data from the samples, result of t he oil content is about 10 to 150 liters/tons of rock with average 56 liters/tons of rock.